Comparative evaluation of methadone administration at different periods in bitches undergoing mastectomy - Uscategui, R. A.R. [UNESP]; Feliciano, M. A.R. [UNESP]; Tiosso, C. F. [UNESP]; Moro, J. V. [UNESP]; Coutinho, L. N.; Brito, M. B.S. [UNESP]; Vicente, W. R.R. [UNESP] (My University, 2017)
This study aimed to evaluate pain, anesthetic requirements, and cardiorespiratory variables in bitches subjected to mastectomy that received methadone pre, trans, or postoperatively. Thirty-six bitches undergoing unilateral mastectomy were randomly allocated into 3 groups in a prospective blind clinical trial. Preoperative group (PRE) received 0.5 mg/kg methadone IM 20 minutes prior to anesthesia induction and placebo at the trans and postoperative periods, transoperative group (TRA) received 0.5 mg/kg methadone IM 20 minutes after skin incision and placebo at others periods, and the postoperative group (POS) received 0.5 mg/kg methadone IM once surgery was completed and placebo at other periods. Propofol dose was needed for anesthetic induction (PDI). Heart (HR) and respiratory rate (fR), mean arterial pressure (MAP), blood oxygen saturation (SpO2), end tidal CO2 pressure (EtCO2), and isoflurane concentration (EtISO) were evaluated every 10 minutes until the end of the surgical procedure. Pain intensity (Melbourne Pain Scale) and rescue analgesia requirements were evaluated for six hours after surgery. Postoperative pain was lower in PRE and TRA (P=0.036); however, no differences (P=0.410) were observed in postoperative rescue analgesia requirements between the groups, even though only 8% of PRE and TRA patients required it against 25% in POS. MAP and EtCO2 were higher (P < 0.001) in PRE and TRA, while EtISO was lower (P < 0.001). PRE showed lower PDI (P=0.016) and HR (P=0.003). In conclusion, pre and transoperative methadone administration result in preemptive pain relief, reduce anesthetic requirements, and consequently cause less cardiovascular depression in bitches undergoing mastectomy, although it possibly leads to hypoventilation.
Keywords: Anesthetic requirements; Anesthetic sparring; NMDA antagonist Opioids; Pain; Preemptive analgesia